Preparation method of printable curved perovskite solar cell

By depositing a porous electron transport layer, an insulating spacer layer and a back electrode layer on the curved conductive substrate, and fixing the coating with a hot melt adhesive film, the problem of difficulty in preparing curved perovskite solar cells in the prior art is solved, and high uniformity and wide application effects are achieved.

CN115039245BActive Publication Date: 2025-04-01HUBEI WONDER SOLAR LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080061401.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-17
Publication Date
2025-04-01
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

It is difficult to prepare curved perovskite solar cells in the prior art, and traditional planar substrate preparation methods cannot meet the needs of curved structures.

Method used

The surface perovskite solar cells are prepared by printing technology. By depositing a porous electron transport layer, a porous insulating spacer layer and a porous back electrode layer on the curved conductive substrate, and fixing the coating with a hot melt adhesive film to ensure the uniformity of each functional layer.

Benefits of technology

It realizes high uniformity preparation of curved perovskite solar cells, expands the application range of perovskite solar cells, and is especially suitable for the integration of portable power supplies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115039245B_ABST
    Figure CN115039245B_ABST
Patent Text Reader

Abstract

The present invention provides a printable curved perovskite solar cell, which comprises a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer and a perovskite filler; the curved conductive substrate comprises a curved transparent substrate and a conductive layer deposited on the curved transparent substrate; the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer are sequentially deposited on the conductive layer from bottom to top; the perovskite filler is filled in the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer. The solar cell is easy to integrate with other items. The present invention also provides a method for preparing the above-mentioned printable curved perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a printable curved surface perovskite solar cell and also relates to a preparation method of the printable curved surface perovskite solar cell. Background Art

[0002] With the rapid development of society, human demand for energy continues to increase, which has led to the continuous adjustment of energy supply forms, gradually transitioning from fossil energy to electric energy. At present, the increasing popularity of electrified and intelligent equipment has brought convenience to our lives, but also put forward more requirements for the diversification of power supply forms. The development of portable self-generating power sources is of great significance to various electronic terminal products used in daily life, which can effectively make up for the problem of short battery life of energy storage power sources. Since solar energy is inexhaustible and widely distributed, solar cells are considered to be portable self-generating power sources with great potential.

[0003] Mainstream solar cell technology is mainly used in large-scale photovoltaic power stations to realize large-scale power generation systems, while the development of portable solar cell technology is relatively backward. Considering the troubles caused by low car battery, exhausted mobile phone battery, and urgent need for electricity for outdoor activities, it is very important to develop portable solar cell technology, especially integrating solar cells with car roofs, mobile phone shells, portable tents, etc., which can play an important role at specific moments, and therefore has important development prospects and can bring significant economic benefits.

[0004] The current mainstream crystalline silicon solar cell technology is mature, but there are great challenges in integrating it with other devices and making it into a portable power source, which is mainly limited by the mechanical properties of the silicon-based material itself. Organic solar cell technology has significant technical advantages in integration into portable power sources, but the poor photoelectric conversion efficiency of organic solar cells restricts its application. Perovskite materials have the advantages of excellent semiconductor properties and processing properties of both inorganic semiconductor materials and organic semiconductor materials, which has enabled perovskite solar cell technology to develop rapidly. The photoelectric conversion efficiency of perovskite solar cells based on planar substrates has broken through to 25.2%. Therefore, it is of great significance to develop integration technology of perovskite solar cells with other devices.

[0005] CN107146847A discloses a carbon-counter electrode perovskite solar cell, which includes a transparent conductive substrate, a photoanode, an insulating layer, a first carbon layer and a second carbon layer from bottom to top, wherein the first carbon layer is a porous carbon layer and the second carbon layer is a low-temperature carbon layer. The preparation method of the perovskite solar cell includes the following steps: (1) preparing a dense layer on the transparent conductive substrate; (2) preparing a TiO2 mesoporous layer and a ZrO2 insulating layer on the dense layer in sequence by screen printing; (3) preparing a porous first carbon layer on the insulating layer; (4) dripping a perovskite precursor slurry onto the surface of the first carbon layer to fill it into the dense layer, the TiO2 mesoporous layer, the ZrO2 insulating layer and the porous film layers of each layer of the first carbon layer; (5) preparing a second carbon layer on the first carbon layer. The substrate of the above perovskite solar cell is in the form of a flat plate. The above preparation method cannot prepare a curved perovskite solar cell.

[0006] CN108550705A discloses a perovskite solar cell module, including a conductive substrate, a perovskite light-absorbing layer and a counter electrode; a hole blocking layer, an electron transport layer and an insulating layer are provided between the conductive substrate and the perovskite light-absorbing layer; a hole transport layer is provided between the counter electrode and the perovskite light-absorbing layer. The preparation method of the perovskite solar cell comprises the following steps: preparing a TiO2 dense layer on an FTO glass substrate; screen-printing titanium dioxide slurry as an electron transport layer on the dense layer, wherein the solvent is pine alcohol; screen-printing zirconium dioxide slurry on the electron transport layer, wherein the solvent is pine alcohol; preparing a CH3NH3PbI3 perovskite precursor slurry with dimethyl sulfoxide and DMF as solvents, and preparing a perovskite light-absorbing layer by spin coating; screen-printing carbon slurry as a hole transport layer on the perovskite light-absorbing layer, wherein the solvent is pine alcohol, and the counter electrode is formed by a room temperature release conductive tape to obtain a perovskite solar cell. The above perovskite solar cell needs to be provided with a hole blocking layer and a hole transport layer, and the substrate is in a flat plate shape. The above preparation method cannot prepare a curved perovskite solar cell. Summary of the invention

[0007] One object of the present invention is to provide a printable curved perovskite solar cell, whose substrate is a curved surface. Such a cell is easy to integrate with other items, expanding the scope of use of the perovskite solar cell. Another object of the present invention is to provide a method for preparing a printable curved perovskite solar cell, which method can prepare a curved perovskite solar cell. Furthermore, the functional layers of the curved perovskite solar cell prepared by the method have high uniformity.

[0008] In one aspect, the present invention provides a printable curved perovskite solar cell, which includes a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer, and a perovskite filler;

[0009] The curved conductive substrate comprises a curved transparent substrate and a conductive layer deposited on the curved transparent substrate;

[0010] The porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer are sequentially deposited on the conductive layer from bottom to top;

[0011] The perovskite filler is filled in the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer.

[0012] According to the printable curved perovskite solar cell of the present invention, preferably, the thickness of the porous electron transport layer is 300-1000 nm, the thickness of the porous insulating spacer layer is 1-6 μm, and the thickness of the porous back electrode layer is 10-40 μm.

[0013] In another aspect, the present invention provides a method for preparing a printable curved perovskite solar cell, comprising the following steps:

[0014] (1) laser etching a clean curved conductive substrate to form an etching line P1;

[0015] (2) covering the conductive layer of the curved conductive substrate having the etched line P1 with a porous electron transport layer slurry, and then covering the porous electron transport layer slurry with a hot melt adhesive to form a first hot melt adhesive film; removing the first hot melt adhesive film to obtain a first preform having a porous electron transport layer;

[0016] (3) covering the porous insulating spacer layer slurry on the porous electron transport layer of the first preform, and then covering the porous insulating spacer layer slurry with a second hot melt adhesive to form a second hot melt adhesive film; removing the second hot melt adhesive film to obtain a second preform having a porous insulating spacer layer;

[0017] (4) covering the porous back electrode layer slurry on the porous insulating spacer layer of the second preform to form a porous back electrode layer, thereby obtaining a third preform having a porous back electrode layer;

[0018] (5) applying the perovskite precursor slurry onto the porous back electrode layer of the third preform so that the perovskite precursor slurry fills the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer to obtain a printable curved perovskite solar cell.

[0019] According to the preparation method of the present invention, preferably, the first hot melt adhesive and the second hot melt adhesive are independently selected from one of polyurethane, polyolefin elastomer, polyethersulfone resin, copolyamide, ethylene-acrylic acid copolymer or ethylene-vinyl acetate copolymer.

[0020] According to the preparation method of the present invention, preferably, the porous electron transport layer slurry comprises an electron transport material and pineneol, the solid content of the electron transport material in the porous electron transport layer slurry is 2 to 10 wt%; the pineneol contains α-pineneol, and the content of the α-pineneol in the pineneol is above 30 wt%; the electron transport material is selected from one or more of titanium dioxide, tin dioxide, zinc oxide or barium stannate.

[0021] According to the preparation method of the present invention, preferably, the porous insulating spacer layer slurry comprises insulating material, ethyl cellulose and pinene alcohol; wherein the mass ratio of the insulating material to the ethyl cellulose is 1:0.15-0.4, and the mass ratio of the insulating material to the pinene alcohol is 1:2-6; the insulating material is selected from one or more of zirconium dioxide, silicon dioxide, aluminum oxide or barium titanate; the pinene alcohol contains α-pinene alcohol, and the content of the α-pinene alcohol in the pinene alcohol is above 30wt%; the porous back electrode layer slurry comprises graphite, carbon black, zirconium dioxide, ethyl cellulose and pinene alcohol; the mass ratio of the graphite to carbon black is 1:0.15-0.5, the mass ratio of the graphite to zirconium dioxide is 1:0.1-0.5, the mass ratio of the graphite to ethyl cellulose is 1:0.1-0.5, and the mass ratio of the graphite to pinene alcohol is 1:2-6.

[0022] According to the preparation method of the present invention, preferably, the porous insulating spacer layer slurry also includes glacial acetic acid, and the mass ratio of the insulating material to the glacial acetic acid is 1:0.05-1; the porous back electrode layer slurry also includes glacial acetic acid, and the mass ratio of the graphite to the glacial acetic acid is 1:0.01-0.6.

[0023] The preparation method according to the present invention preferably further comprises the following steps:

[0024] The first preform having the porous electron transport layer is annealed at 300-600° C. for 10-60 min and then used in step (3).

[0025] The preparation method according to the present invention preferably further comprises the following steps:

[0026] Laser etching on the second preform having the porous insulating spacer layer to form an etched line P2;

[0027] The etching line P2 is located on the left side of the etching line P1 and is tangent to the etching line P1; the width of the etching line P2 is 0.3-1 mm.

[0028] The preparation method according to the present invention preferably further comprises the following steps:

[0029] Laser etching is performed on the third preform having the porous back electrode layer to form an etched line P3, and then annealing is performed at 300-600° C. for 10-60 min;

[0030] The etching line P3 is located on the left side of the etching line P2 and is tangent to the etching line P2. The width of the etching line P3 is 0.05-0.3 mm.

[0031] The substrate of the printable perovskite solar cell of the present invention is a curved surface, which is convenient for integration with other items (for example, a car roof, a mobile phone housing, a portable tent, etc.), and can be used for portable solar cells, expanding the scope of use of printable perovskite solar cells. The present invention covers the coating slurry with a hot melt adhesive film, so that the coating slurry can be fixed on the curved substrate, preventing the coating slurry from being deposited along the curvature of the substrate, and improving the uniformity of each functional layer. According to the preferred technical solution of the present invention, by regulating the composition of the coating slurry, the coating slurry has a suitable fluidity, and the uniformity of each functional layer is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a physical picture of the printable curved perovskite solar cell obtained in Example 1.

[0033] Figure 2 It is a schematic diagram of the structure of a printable curved perovskite solar cell of the present invention.

[0034] Figure 3 The graph of the viscosity of the porous electron transport layer slurry of Example 1 and Example 2 as a function of temperature.

[0035] Figure 4 The graph of the viscosity of the porous insulating spacer layer slurry of Example 1 and Example 2 as a function of temperature.

[0036] Figure 5 (A) is a top view of the three-dimensional contour morphology of the porous electron transport layer of Example 1.

[0037] Figure 5 (B) is a front view of the three-dimensional contour morphology of the porous electron transport layer of Example 1.

[0038] Figure 6 (A) is a top view of the three-dimensional contour morphology of the porous electron transport layer of Example 2.

[0039] Figure 6 (B) is a front view of the three-dimensional contour morphology of the porous electron transport layer of Example 2.

[0040] Figure 7 (A) is a top view of the three-dimensional contour morphology of the multiple insulating spacer layers of Example 1.

[0041] Figure 7 (B) is a front view of the three-dimensional contour morphology of the multiple insulating spacer layers of Example 1.

[0042] Figure 8 (A) is a top view of the three-dimensional contour morphology of the multiple insulating spacer layers of Example 2.

[0043] Figure 8 (B) is a front view of the three-dimensional contour morphology of the multiple insulating spacer layers of Example 2.

[0044] The reference numerals are as follows:

[0045] 1-curved transparent substrate; 2-conductive layer; 3-porous electron transport layer; 4-porous insulating spacer layer; 5-porous back electrode layer. DETAILED DESCRIPTION

[0046] The present invention is described in detail below, but the present invention is not limited thereto.

[0047] <Printable curved perovskite solar cells>

[0048] like Figure 1 As shown, the substrate of the printable curved perovskite solar cell of the present invention has a certain curvature. This is different from the existing printable perovskite solar cells with a planar material as the substrate. Since its substrate has a certain curvature, the fluidity of the printed wet film is greatly increased, which causes great difficulties in the preparation of the perovskite solar cell. Although printable planar perovskite solar cells have been widely used, printable curved perovskite solar cells have not yet been reported.

[0049] The printable curved perovskite solar cell of the present invention comprises a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer and a perovskite filler. In fact, the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer are also curved structures. The perovskite filler is filled in the gaps of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer. The printable perovskite solar cell of the present invention may also include an encapsulation layer. In some embodiments, the printable curved perovskite solar cell consists of a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer and a perovskite filler. In other embodiments, the printable curved perovskite solar cell consists of a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer, a perovskite filler and an encapsulation layer.

[0050] Curved conductive substrate

[0051] The curved conductive substrate of the present invention may include a curved transparent substrate and a conductive layer. The conductive layer may be deposited on the curved transparent substrate. Preferably, the curved conductive substrate of the present invention is composed of a curved transparent substrate and a conductive layer deposited on the curved transparent substrate. The so-called "curved surface" refers to the trajectory formed by a moving line moving continuously in space. The curved surface of the present invention may be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface.

[0052] The curved transparent substrate can be transparent glass or transparent polymer. Examples of transparent polymers include, but are not limited to, polyvinyl chloride, polymethyl methacrylate, polycarbonate, polystyrene, polyethylene, and ethylene-vinyl acetate copolymer. According to one embodiment of the present invention, the curved transparent substrate is transparent glass.

[0053] The conductive layer may be formed of fluorine-doped tin oxide, tin-doped indium oxide, aluminum-doped zinc oxide, graphene, a transparent metal conductive film, etc. According to one embodiment of the present invention, the conductive layer is formed of fluorine-doped tin oxide.

[0054] Porous electron transport layer

[0055] The porous electron transport layer of the present invention can be deposited on the conductive layer. The porous electron transport layer can also be a curved surface. The curved surface of the present invention can be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface.

[0056] The porous electron transport layer may be formed of titanium dioxide, tin dioxide, zinc oxide or barium stannate. According to one embodiment of the present invention, the porous electron transport layer is formed of titanium dioxide. The thickness of the porous electron transport layer may be 300 to 1000 nm; preferably 400 to 800 nm; more preferably 500 to 600 nm. The pore size of the porous electron transport layer may be 2 to 100 nm; preferably 15 to 50 nm; more preferably 25 to 35 nm. The grain size of the porous electron transport layer may be 10 to 50 nm; preferably 15 to 35 nm; more preferably 25 to 35 nm.

[0057] Porous insulation spacer

[0058] The porous insulating spacer layer of the present invention can be deposited on the porous electron transport layer. The porous insulating spacer layer can also be a curved surface. The curved surface of the present invention can be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface.

[0059] The porous insulating spacer layer may be formed of zirconium dioxide, silicon dioxide, aluminum oxide or barium titanate. According to one embodiment of the present invention, the porous insulating spacer layer is formed of zirconium dioxide. The thickness of the porous insulating spacer layer may be 1 to 6 μm; preferably 2 to 5 μm; more preferably 3 to 4 μm. The pore size of the porous electron transport layer may be 10 to 500 nm; preferably 30 to 200 nm; more preferably 50 to 100 nm. The grain size of the porous insulating spacer layer may be 10 to 500 nm; preferably 30 to 200 nm; more preferably 100 to 200 nm.

[0060] Porous back electrode layer

[0061] The porous back electrode layer of the present invention can be deposited on the porous insulating spacer layer. The porous back electrode layer is also a curved surface. The curved surface of the present invention can be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface.

[0062] The porous back electrode layer can be formed from a raw material including a porous electrode material. The porous electrode material can be a porous carbon electrode material or a porous conductive oxide electrode material. Examples of porous carbon electrode materials include, but are not limited to, graphite, carbon black, activated carbon, graphene, and carbon nanotubes. Porous conductive oxide electrode materials include, but are not limited to, fluorine-doped tin oxide, tin-doped indium oxide, and aluminum-doped zinc oxide. According to one embodiment of the present invention, the porous back electrode layer is formed of graphite, carbon black, and zirconium oxide. The mass ratio of graphite to carbon black can be 1:0.15 to 0.5; preferably 1:0.25 to 0.4; more preferably 1:0.3 to 0.35. The mass ratio of graphite to zirconium dioxide can be 1:0.1 to 0.5; preferably 1:0.1 to 0.3; more preferably 1:0.15 to 0.2. This can achieve better curing and strengthening effects, thereby improving the quality of the membrane, and then improving the electrical properties and filling properties of the membrane.

[0063] The thickness of the porous back electrode layer may be 10-50 μm, preferably 15-40 μm, and more preferably 20-30 μm. The size of the porous back electrode graphite sheet may be 1-100 μm, preferably 5-50 μm, and more preferably 10-20 μm.

[0064] Perovskite fillers

[0065] The perovskite filler of the present invention is filled in the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back plate electrode layer. The perovskite filler is a compound having a structure as shown in formula (I).

[0066] ABX3(I)

[0067] Wherein, A is selected from cations formed by alkylamine, formamidine or alkali metal; preferably, A is selected from cations formed by methylamine, formamidine, cesium or rubidium. More preferably, A is a cation formed by methylamine. B is selected from cations formed by lead or tin. Preferably, B is a cation formed by lead. X is selected from anions formed by iodine, bromine, chlorine or halogen-like elements. Examples of halogen-like elements include, but are not limited to, cyanogen, thiocyanate, selenium cyanogen, oxygen cyanogen, azide carbon disulfide. Preferably, X is an iodide ion. According to one embodiment of the present invention, the compound having a perovskite structure is iodine lead methylamine (CH3NH3PbI3).

[0068] Encapsulation layer

[0069] The encapsulation layer of the present invention may include a hot melt adhesive film and a flexible backplane. The hot melt adhesive film is covered on the porous back electrode layer. The flexible backplane is covered on the hot melt adhesive film. The hot melt adhesive film of the present invention may be formed of polyurethane or ethylene-vinyl acetate copolymer. The hot melt adhesive film may also be a curved surface. The curved surface of the present invention may be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface. The flexible backplane of the present invention may be a flexible functional film with waterproof insulation effect. The flexible backplane may also be a curved surface. The curved surface of the present invention may be a ruled surface or a hyperbolic surface. The ruled surface includes but is not limited to one of a cylindrical surface, a conical surface, an elliptical cylindrical surface, an elliptical conical surface, a conical surface or a cylindrical surface. The hyperbolic surface includes but is not limited to a spherical surface and a torus. According to one embodiment of the present invention, the curved surface is a cylindrical surface.

[0070] <Preparation method>

[0071] The preparation method of the curved perovskite solar cell of the present invention comprises the following steps: (1) forming an etching line P1; (2) forming a porous electron transport layer; (3) forming a porous insulating spacer layer; (4) forming a porous back electrode layer; (5) filling perovskite. Optionally, the preparation method of the present invention further comprises (6) a packaging step. In the present invention, the porous electron transport layer, the porous insulating spacer layer, and the porous back electrode layer can be annealed separately, or two of them can be annealed together, or three layers can be annealed together. A detailed description is given below.

[0072] Steps for forming etching line P1

[0073] The cleaned curved conductive substrate is laser etched to form an etched line P1.

[0074] Before laser etching, the curved conductive substrate needs to be cleaned. The cleaned curved conductive substrate refers to the curved conductive substrate after removing surface stains. The curved conductive substrate is ultrasonically cleaned in a cleaning agent, and then cleaned in ethanol. The cleaned curved conductive substrate is dried to obtain a clean curved conductive substrate. The cleaning agent can be selected from Dettol, Mr. Wei Meng, Jie Shiqi, LOPO, Jingan, White Cat, Liby, Kleen MCT511 and III cleaning solution; preferably, the cleaning agent is selected from Jingan, Baimao, Libai, Kleen MCT511 and III cleaning solution in one or more; more preferably III cleaning solution. The ultrasonic cleaning time in the cleaning agent can be 5 to 30 minutes; preferably 10 to 25 minutes; more preferably 15 to 20 minutes. The ultrasonic cleaning time in ethanol can be 1 to 20 minutes; preferably 3 to 15 minutes; more preferably 3 to 10 minutes. The drying temperature can be 50 to 80°C; preferably 55 to 75°C; more preferably 55 to 60°C. This can make the stains on the curved conductive substrate removed more thoroughly.

[0075] A nanosecond laser etcher may be used to laser-etch the curved conductive substrate to form an etched line P1. The width of the etched line P1 may be 0.02 to 0.15 mm, preferably 0.03 to 0.1 mm, and more preferably 0.05 to 0.1 mm.

[0076] The curved conductive substrate with the etching line P1 is cleaned. Specifically, the curved conductive substrate with the etching line P1 is placed in deionized water for ultrasonic cleaning, and then placed in ethanol for ultrasonic cleaning. The cleaned curved conductive substrate is dried until there is no moisture and spot impurities on its surface. The time for ultrasonic cleaning in deionized water can be 5 to 30 minutes; preferably 10 to 25 minutes; more preferably 15 to 20 minutes. The time for ultrasonic cleaning in ethanol can be 1 to 20 minutes; preferably 3 to 15 minutes; more preferably 3 to 10 minutes. The drying temperature can be 50 to 80°C; preferably 55 to 75°C; more preferably 60 to 70°C. In this way, the cleanliness of the part to be deposited is ensured to ensure the smooth progress of the subsequent steps.

[0077] The cleaned curved conductive substrate with the etching line P1 is treated with ultraviolet and ozone. The treatment time can be 5 to 30 minutes, preferably 10 to 20 minutes, and more preferably 10 to 15 minutes. Ultraviolet and ozone can clean organic matter on the surface of the curved conductive substrate and improve the wettability of the surface of the curved conductive substrate.

[0078] Steps for forming a porous electron transport layer

[0079] The porous electron transport layer slurry is covered on the conductive layer of the curved conductive substrate with the etching line P1, and then the hot melt adhesive is covered on the porous electron transport layer slurry to form a first hot melt adhesive film; after removing the first hot melt adhesive film, a first preform with a porous electron transport layer is obtained. Specifically, the porous electron transport layer slurry is evenly covered on the conductive layer of the curved conductive substrate with the etching line P1, and then the first hot melt adhesive is evenly covered on the porous electron transport layer slurry, and the first hot melt adhesive film is obtained after drying, and the first hot melt adhesive film is removed to obtain a first preform with a porous electron transport layer. There is no particular limitation on the method of removing the first hot melt adhesive film, and conventional methods in the art can be used.

[0080] The porous electron transport layer slurry can be coated on the conductive layer of the curved conductive substrate having the etched line P1 by screen printing, slit coating, doctor blading, inkjet printing, spray deposition and other techniques. According to one embodiment of the present invention, the porous electron transport layer slurry is printed on the conductive layer of the curved conductive substrate having the etched line P1 by screen printing technology. The screen printing technology can be implemented by a curved screen printer.

[0081] The porous electron transport layer slurry may include an electron transport material and pinene alcohol. The electron transport material may be selected from one of titanium dioxide, tin dioxide, zinc oxide or barium stannate. Preferably, the electron transport material is titanium dioxide. The pore size of the electron transport material may be 2 to 50 nm; preferably 15 to 35 nm; more preferably 25 to 35 nm. The grain size of the electron transport material may be 10 to 40 nm; preferably 15 to 35 nm; more preferably 25 to 35 nm. The pinene alcohol may be selected from one or more of α-pinene alcohol, β-pinene alcohol or γ-pinene alcohol. Preferably, pinene alcohol contains α-pinene alcohol. More preferably, the pinene alcohol is α-pinene alcohol. The amount of α-pinene alcohol in pinene alcohol is 30 wt% or more; preferably 80 wt% or more; more preferably 90 wt% or more. The slurry prepared with α-pinene alcohol is jelly-like at room temperature, but has good fluidity when the temperature is greater than 40°C, which is conducive to forming a uniform porous electron transport layer on a curved conductive substrate. According to one embodiment of the present invention, the porous electron transport layer slurry includes titanium dioxide and α-pinene alcohol. Titanium dioxide can be provided by titanium dioxide slurry. Titanium dioxide slurry can be purchased from Greatcellsolar. Preferably, the titanium dioxide slurry is selected from NR-18 or NR30 of Greatcellsolar. According to one embodiment of the present invention, the titanium dioxide slurry is a titanium dioxide slurry with a model of NR-30 purchased from Greatcellsolar. The solid content of the electron transport material in the porous electron transport layer slurry can be 2 to 10 wt%; preferably 3 to 7 wt%; more preferably 4 to 5 wt%.

[0082] The porous electron transport layer slurry is prepared by mixing. Preferably, a vacuum degassing step is further included after mixing. The vacuum degassing time can be 20 to 80 minutes, preferably 30 to 70 minutes, and more preferably 40 to 50 minutes. This can improve the uniformity of film formation.

[0083] After the porous electron transport layer slurry is covered on the conductive layer of the curved conductive substrate with the etching line P1, it can be left to stand at room temperature for 3 to 20 minutes, preferably 5 to 15 minutes, and more preferably 10 to 15 minutes; then the first hot melt adhesive is coated on the porous electron transport layer slurry. The first hot melt adhesive can also be coated first and then left to stand at room temperature. In addition, the first hot melt adhesive can be directly coated without standing at room temperature. Standing can increase the flatness of the film surface, and the film that has not been stood is relatively rough.

[0084] The first hot melt adhesive can be selected from one of polyurethane hot melt adhesive, polyolefin elastomer, polyethersulfone resin, copolyamide, ethylene-acrylic acid copolymer, and ethylene-vinyl acetate copolymer hot melt adhesive. Preferably, the first hot melt adhesive is a polyurethane hot melt adhesive. More preferably, the first hot melt adhesive is selected from one of the HSL-U60 hot melt adhesive of Shenzhen Hengshenglong Adhesive Products Co., Ltd., the XJU-5C hot melt adhesive of Shanghai Xingxia Polymer Products Co., Ltd., and the LV368B-10-FQ hot melt adhesive of Jiangsu Hehe New Materials Co., Ltd. According to one embodiment of the present invention, the first hot melt adhesive is the XJU-5C hot melt adhesive of Shanghai Xingxia Polymer Products Co., Ltd. The first hot melt adhesive can assist in fixing the porous electron transport layer slurry on the curved conductive substrate, improve the uniformity of the porous electron transport layer, facilitate removal after drying, and will not affect the performance of the perovskite solar cell.

[0085] The drying can be carried out in a vacuum drying oven. The drying temperature can be 80 to 130°C, preferably 90 to 120°C, and more preferably 90 to 110°C. The drying time can be 5 to 20 minutes, preferably 10 to 20 minutes, and more preferably 13 to 17 minutes. In this way, the hot melt adhesive can be formed into a solid film for easy removal, and the porous electron transport layer can be deposited on the curved conductive substrate.

[0086] In some embodiments, the first preform having the porous electron transport layer is annealed. The annealing temperature may be 300 to 600° C., preferably 400 to 600° C., and more preferably 450 to 550° C. The annealing time may be 10 to 60 min, preferably 20 to 50 min, and more preferably 20 to 40 min. This may enhance the performance of the porous electron transport layer.

[0087] Steps for forming a porous insulating spacer layer

[0088] The porous insulating spacer layer slurry is covered on the porous electron transport layer of the first preform, and then the second hot melt adhesive is covered on the porous insulating spacer layer slurry to form a second hot melt adhesive film; after removing the second hot melt adhesive film, a second preform having a porous insulating spacer layer is obtained. Specifically, the porous electron transport layer of the first preform is covered with the porous insulating spacer layer slurry, and then the second hot melt adhesive is evenly covered on the porous insulating spacer layer, and after drying, a second hot melt adhesive film is formed; the second hot melt adhesive film is removed to obtain a second preform having a porous insulating spacer layer. There is no particular limitation on the method of removing the second hot melt adhesive film, and conventional methods in the art can be used.

[0089] The porous insulating spacer layer slurry can be coated on the porous electron transport layer of the first preform by screen printing, slit coating, doctor blading, inkjet printing, spray deposition and other techniques. According to one embodiment of the present invention, the porous insulating spacer layer slurry is printed on the porous electron transport layer of the first preform by screen printing. The screen printing technique can be implemented by a curved screen printer.

[0090] The porous insulating spacer layer slurry may include insulating material, ethyl cellulose and pine alcohol. In some embodiments, the porous insulating spacer layer slurry may also include glacial acetic acid. The porous insulating spacer layer slurry may be prepared by planetary ball mill dispersion, high-speed shearing machine shearing dispersion, sand mill dispersion, self-rotation and revolution mixer, nano-crushing dispersion and other processes. In addition, a vacuum degassing step may be included. The vacuum degassing time may be 20 to 80 minutes; preferably 30 to 70 minutes; more preferably 40 to 50 minutes. This can improve the uniformity of film formation.

[0091] The insulating material may be selected from one of zirconium dioxide, silicon dioxide, aluminum oxide or barium titanate. Preferably, the insulating material is zirconium dioxide. The insulating material has a porous structure, and its pore size may be 10 to 500 nm, preferably 30 to 200 nm, and more preferably 50 to 100 nm. The grain size of the raw material having the insulating function may be 10 to 500 nm, preferably 30 to 200 nm, and more preferably 50 to 200 nm.

[0092] The viscosity of ethyl cellulose can be 8 to 60 cP (centipoise), preferably 10 to 55 cP, and more preferably 10 to 46 cP (centipoise). Ethyl cellulose can be selected from one or more of ethyl cellulose with a viscosity of 10 cP, ethyl cellulose with a viscosity of 20 cP, ethyl cellulose with a viscosity of 46 cP, or ethyl cellulose with a viscosity of 55 cP. Preferably, ethyl cellulose is selected from one or more of ethyl cellulose with a viscosity of 10 cP or ethyl cellulose with a viscosity of 46 cP. More preferably, ethyl cellulose is a mixture of ethyl cellulose with a viscosity of 10 cP and ethyl cellulose with a viscosity of 46 cP. The mass ratio of ethyl cellulose with a viscosity of 10 cP and ethyl cellulose with a viscosity of 46 cP can be 1:0.01 to 1; preferably 1:0.3 to 1; more preferably 1:0.5 to 1. This is enough to adjust the fluidity of the porous insulating spacer layer slurry and improve the uniformity of the porous insulating spacer layer.

[0093] The pine alcohol can be selected from one or more of α-pine alcohol, β-pine alcohol or γ-pine alcohol. Preferably, the pine alcohol contains α-pine alcohol. More preferably, the pine alcohol is α-pine alcohol. The amount of α-pine alcohol in the pine alcohol is 30wt% or more; preferably 80wt% or more; more preferably 90wt% or more. The slurry prepared with α-pine alcohol is jelly-like at room temperature, but has good fluidity when the temperature is greater than 40°C, which is conducive to forming a uniform porous insulating spacer layer on a curved conductive substrate.

[0094] The mass ratio of the insulating material to the ethyl cellulose may be 1:0.15-0.4, preferably 1:0.2-0.35, and more preferably 1:0.25-0.3. This can improve the fluidity of the porous insulating spacer slurry and the uniformity of the porous insulating spacer.

[0095] The mass ratio of the insulating material to terpineol can be 1:2 to 6, preferably 1:2 to 5, and more preferably 1:3 to 5. This can improve the fluidity of the porous insulating spacer slurry and improve the uniformity of the porous insulating spacer.

[0096] The mass ratio of the insulating material to the glacial acetic acid can be 1:0.05 to 1, preferably 1:0.2 to 0.8, and more preferably 1:0.3 to 0.6. Glacial acetic acid can improve the dispersibility of the slurry and the stability of the slurry, thereby improving the uniformity of the porous insulating spacer layer.

[0097] After the porous insulating spacer layer slurry is covered on the porous electron transport layer of the first preform, it is first allowed to stand at room temperature for 3 to 20 minutes, preferably 5 to 15 minutes, and more preferably 10 to 15 minutes; then the first hot melt adhesive is coated on the porous electron transport layer slurry. The first hot melt adhesive can also be coated first and then allowed to stand at room temperature. Alternatively, the first hot melt adhesive can be directly coated without standing. Standing can increase the flatness of the film surface, and the film that has not been stood is relatively rough. The second hot melt adhesive can be selected from one of polyurethane hot melt adhesive, polyolefin elastomer, polyethersulfone resin, copolyamide, ethylene-acrylic acid copolymer, and ethylene-vinyl acetate copolymer hot melt adhesive. Preferably, the second hot melt adhesive is a polyurethane hot melt adhesive. More preferably, the second hot melt adhesive is selected from one of the HSL-U60 hot melt adhesive of Shenzhen Hengshenglong Adhesive Products Co., Ltd., the XJU-5C hot melt adhesive of Shanghai Xingxia Polymer Products Co., Ltd., and the LV368B-10-FQ hot melt adhesive of Jiangsu Hehe New Materials Co., Ltd. According to one embodiment of the present invention, the second hot melt adhesive is XJU-5C hot melt adhesive produced by Shanghai Xingxia Polymer Products Co., Ltd. The second hot melt adhesive can fix the porous insulating spacer slurry on the curved conductive substrate, improve the uniformity of the porous insulating spacer layer, facilitate removal after drying, and will not affect the performance of the perovskite solar cell.

[0098] The drying can be carried out in a vacuum drying oven. The drying temperature can be 80-130°C, preferably 90-120°C, and more preferably 90-110°C. The drying time can be 5-20 minutes, preferably 10-20 minutes, and more preferably 13-17 minutes. In this way, the second hot melt adhesive can be formed into a solid film for easy removal, and the porous insulating spacer layer can be deposited on the curved conductive substrate.

[0099] In some embodiments, laser etching is performed on the second preform having the porous insulating spacer layer to form an etched line P2. The etched line P2 is located on the left side of the etched line P1 and is tangent to the etched line P1. The width of the etched line P2 may be 0.3 to 1 mm, preferably 0.4 to 0.7 mm, and more preferably 0.4 to 0.6 mm.

[0100] In some embodiments, the second preform with the porous insulating spacer layer is annealed or the second preform with the etched line P2 is annealed. The annealing temperature may be 300-600° C., preferably 400-600° C., and more preferably 450-550° C. The annealing time may be 10-60 min, preferably 20-50 min, and more preferably 20-40 min. This may enhance the performance of the porous insulating spacer layer.

[0101] Steps for forming a porous back electrode layer

[0102] The porous back electrode layer slurry is covered on the porous insulating spacer layer of the second preform to form a porous back electrode layer, thereby obtaining a third preform having a porous back electrode layer. Specifically, the porous back electrode layer slurry is covered on the porous insulating spacer layer of the second preform, and after drying, a porous back electrode layer is formed, thereby obtaining a third preform having a porous back electrode layer.

[0103] The porous back electrode layer slurry can be coated on the porous insulating spacer layer of the second preform by screen printing, slit coating, doctor blade coating, inkjet printing, spray deposition and other techniques. According to one embodiment of the present invention, the porous back electrode layer slurry is printed on the porous insulating spacer layer of the second preform by screen printing. The screen printing technique can be implemented by a curved screen printer.

[0104] The porous back electrode layer slurry may include a porous electrode material, zirconium dioxide, ethyl cellulose and terpineol. In some embodiments, the porous back electrode layer slurry may also include glacial acetic acid. The porous back electrode layer slurry may be prepared by planetary ball milling dispersion, high-speed shearing dispersion, sand mill dispersion, self-rotation and revolution mixer nano-crushing dispersion and the like.

[0105] The porous electrode material may be selected from one or more of graphite, carbon black, activated carbon, graphene, carbon nanotubes, fluorine-doped tin oxide, tin-doped indium oxide, and aluminum-doped zinc oxide. According to one embodiment of the present invention, the porous electrode material is a mixture of graphite and carbon black. The mass ratio of graphite to carbon black may be 1:0.15 to 0.5; preferably 1:0.25 to 0.4; more preferably 1:0.3 to 0.35. The particle size of the graphite may be 1 to 100 μm; preferably 5 to 50 μm; more preferably 10 to 20 μm.

[0106] Zirconium dioxide is zirconium dioxide powder. The grain size of zirconium dioxide can be 10 to 500 nm; preferably 30 to 200 nm; more preferably 100 to 200 nm. The mass ratio of graphite to zirconium dioxide can be 1:0.1 to 0.5; preferably 1:0.1 to 0.3; more preferably 1:0.15 to 0.2. Zirconium dioxide can play a role in strengthening and curing, improve the quality of the film after sintering, and thus improve the electrical properties and filling properties of the back electrode layer.

[0107] The viscosity of ethyl cellulose may be 8 to 60 cP (centipoise), preferably 10 to 55 cP, and more preferably 10 to 46 cP (centipoise). Ethyl cellulose may be selected from one or more of ethyl cellulose having a viscosity of 10 cP, ethyl cellulose having a viscosity of 20 cP, ethyl cellulose having a viscosity of 46 cP, or ethyl cellulose having a viscosity of 55 cP. Preferably, ethyl cellulose is selected from one or more of ethyl cellulose having a viscosity of 10 cP or ethyl cellulose having a viscosity of 46 cP. More preferably, ethyl cellulose is a mixture of ethyl cellulose having a viscosity of 10 cP and ethyl cellulose having a viscosity of 46 cP. The mass ratio of ethyl cellulose having a viscosity of 10 cP to ethyl cellulose having a viscosity of 46 cP may be 1:0.01 to 3; preferably 1:0.05 to 2; more preferably 1:0.7 to 1.2. The mass ratio of graphite to ethyl cellulose may be 1:0.1 to 0.5; preferably 1:0.1 to 0.3; more preferably 1:0.15 to 0.2. In this way, the porous back electrode layer can be firmly deposited on the curved conductive substrate, and the fluidity of the porous back electrode layer slurry can be adjusted to improve the uniformity of the porous back electrode layer.

[0108] The pine alcohol can be selected from one or more of α-pine alcohol, β-pine alcohol or γ-pine alcohol; preferably α-pine alcohol and γ-pine alcohol. The mass ratio of α-pine alcohol to γ-pine alcohol can be 1:0.01-3; preferably 1:0.5-2; more preferably 1:0.8-1.3. This is conducive to forming a uniform porous back electrode layer on a curved conductive substrate. The mass ratio of graphite to pine alcohol can be 1:2-6; preferably 1:2-5; more preferably 1:3-5. This can improve the fluidity of the porous back electrode layer slurry and improve the uniformity of the porous back electrode layer.

[0109] The mass ratio of graphite to glacial acetic acid can be 1:0.01 to 0.6, preferably 1:0.05 to 0.4, and more preferably 1:0.1 to 0.2. Glacial acetic acid can improve the dispersibility of the slurry and the stability of the slurry, thereby improving the uniformity of the porous back electrode layer.

[0110] The drying can be carried out in a vacuum drying oven. The drying temperature can be 80 to 130° C., preferably 90 to 120° C., and more preferably 90 to 10° C. The drying time can be 5 to 20 minutes, preferably 10 to 20 minutes, and more preferably 13 to 17 minutes.

[0111] In some embodiments, laser etching is performed on the third preform having the porous back electrode layer to form an etched line P3. The etched line P3 is located on the left side of the etched line P2 and is tangent to the etched line P2. The width of the etched line P3 may be 0.05 to 0.3 mm, preferably 0.07 to 0.14 mm, and more preferably 0.08 to 0.12 mm.

[0112] In some embodiments, the third preform of the porous back electrode layer is annealed or the third preform having the etched line P3 is annealed. The annealing temperature may be 300-600°C, preferably 300-500°C, and more preferably 350-450°C. The annealing time may be 10-60 min, preferably 20-50 min, and more preferably 20-40 min. This can enhance the mechanical properties of the porous mesoporous film to facilitate the filling of the perovskite precursor slurry.

[0113] Steps to fill the perovskite

[0114] The perovskite precursor slurry is applied to the porous back electrode layer of the third preform so that the perovskite precursor slurry fills the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer to obtain a printable curved perovskite solar cell.

[0115] The perovskite precursor slurry includes a compound having a perovskite structure and a solvent. The compound having a perovskite structure is shown in formula (I):

[0116] ABX3(I).

[0117] A is selected from cations formed by alkylamine, formamidine or alkali metal. Preferably, A is selected from cations formed by methylamine, formamidine, cesium or rubidium. More preferably, A is a cation formed by methylamine. B is selected from cations formed by lead or tin. Preferably, B is a cation formed by lead. X is selected from anions formed by iodine, bromine, chlorine or halogen-like elements. Examples of halogen-like elements include, but are not limited to, cyanide, thiocyanate, selenium cyanide, oxygen cyanide, azide carbon disulfide. Preferably, X is an anion formed by iodine. According to one embodiment of the present invention, the compound having a perovskite structure is iodine lead methylamine (CH3NH3PbI3). The solvent may be selected from one or more of γ-butyrolactone, N,N-dimethylformamide, N-methylformamide, methylpyrrolidone or dimethyl sulfoxide. Preferably, the solvent is selected from one or more of γ-butyrolactone, N,N-dimethylformamide, N-methylformamide. More preferably, the solvent is γ-butyrolactone. The mass fraction of the solute in the perovskite precursor slurry may be 15 to 45 wt %, preferably 20 to 40 wt %, and more preferably 25 to 35 wt %.

[0118] The perovskite precursor slurry can be applied to the porous back electrode layer of the third preform by dispensing. After the perovskite precursor slurry is filled into the porous structure of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer, annealing is performed. The annealing temperature can be 50 to 150° C., preferably 50 to 100° C., and more preferably 50 to 70° C. The annealing time can be 0.5 to 24 hours, preferably 1 to 12 hours, and more preferably 6 to 12 hours.

[0119] Packaging steps

[0120] A hot melt adhesive film is covered on the porous back electrode layer of the printable curved perovskite solar cell, and then a flexible back sheet is placed, and the encapsulation of the printable curved perovskite solar cell is completed after vacuum lamination. The flexible back sheet layer can be a flexible functional film with waterproof insulation effect. The hot melt adhesive film can be a polyurethane hot melt adhesive or an ethylene-vinyl acetate copolymer hot melt adhesive. The coating thickness of the hot melt adhesive film can be 0.3 to 0.8 mm. The vacuum lamination temperature can be 90 to 120° C. The vacuum lamination time can be 5 to 15 minutes.

[0121] The present invention increases the viscosity of the slurry at room temperature by adjusting the proportion of the type and amount of terpineol and ethyl cellulose in the slurry, while maintaining good fluidity of the slurry at the printing temperature, thereby improving the controllability of curved film printing. The printed curved film is fixed by covering the surface with hot melt adhesive, thereby increasing the uniformity of film formation.

[0122] The following is a further description of the implementation of the present invention through specific examples.

[0123] In the following examples and comparative examples, the hot melt adhesive model is XJU-5C, purchased from Shanghai Xingxia Polymer Products Co., Ltd.; the curved screen printer model is ATMAOE67, purchased from Dongyuan Machinery Industry (Kunshan) Co., Ltd.; the nanosecond laser etcher model is ET660, purchased from Wuhan Top Silver Optoelectronics Technology Co., Ltd.; the femtosecond laser etcher model is ETG1370, purchased from Wuhan Yuanlu Optoelectronics Technology Co., Ltd.; the curved conductive substrate is composed of a curved transparent glass substrate and a fluorine-doped tin oxide conductive layer deposited on the curved transparent glass substrate; the titanium dioxide slurry model is NR-30, purchased from Greatcellsolar, Australia, and the grain size of titanium dioxide is 30nm; the grain size of zirconium dioxide powder is 50nm. The particle size of graphite is 15μm.

[0124] Example 1

[0125] Figure 2 Schematic diagram of the structure of a printable curved perovskite solar cell of the present invention. The printable curved perovskite solar cell has a curved conductive substrate. The curved conductive substrate includes a curved transparent substrate 1 and a conductive layer 2 deposited on the curved transparent substrate 1. A porous electron transport layer 3, a porous insulating spacer layer 4 and a porous back electrode layer 5 are sequentially deposited on the conductive layer 2 from bottom to top. The perovskite filler is filled in the pores of the porous electron transport layer 2, the porous insulating spacer layer 3 and the porous back electrode layer 4. The preparation method of the printable curved perovskite solar cell is as follows:

[0126] (1) Place the curved conductive substrate on III cleaning agent, ultrasonic cleaning for 15 minutes; then ultrasonic cleaning in ethanol for 10 minutes. The cleaned curved conductive substrate is dried at 55°C to obtain a clean curved conductive substrate. The cleaned curved conductive substrate is placed on a contoured fixture and fixed by vacuum adsorption. The conductive layer of the curved conductive substrate is laser etched by a nanosecond laser etcher to form an etched line P1. The width of the etched line P1 is 0.08mm. The curved conductive substrate with the etched line P1 is placed in deionized water and ultrasonically cleaned for 15 minutes; then ultrasonically cleaned in ethanol for 5 minutes. The cleaned curved conductive substrate with the etched line P1 is dried at 60°C to remove moisture and spot impurities on its surface. The dried curved conductive substrate with the etched line P1 is treated with ultraviolet and ozone for 15 minutes.

[0127] (2) Mix the raw materials of the porous electron transport layer slurry, vacuum degassing for 45 minutes, and obtain the porous electron transport layer slurry. The composition of the porous electron transport layer slurry is shown in Table 1. The porous electron transport layer slurry is printed on the conductive layer of the curved conductive substrate with the etched line P1 using a screen printing machine. The curved conductive substrate after printing the porous electron transport layer slurry is allowed to stand at room temperature for 10 minutes, and then the polyurethane hot melt adhesive is evenly covered on the porous electron transport layer slurry, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes. After the vacuum drying is completed, the polyurethane film is removed to obtain the first preform having a porous electron transport layer. The first preform having a porous electron transport layer is annealed at 500°C for 30 minutes.

[0128] (3) The raw materials of the porous insulating spacer layer slurry are evenly dispersed by a planetary ball mill, and vacuum degassing is performed for 45 minutes to obtain a porous insulating spacer layer slurry. The composition of the porous insulating spacer layer slurry is shown in Table 2. The porous insulating spacer layer slurry is printed on the porous electron transport layer of the first preform by a screen printing machine. The first preform after printing the porous insulating spacer layer slurry is allowed to stand at room temperature for 10 minutes, and then the polyurethane hot melt adhesive is evenly covered on the porous insulating spacer layer slurry, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes. After the vacuum drying is completed, the polyurethane film is removed to obtain a second preform with a porous insulating spacer layer.

[0129] (4) The porous back electrode layer slurry is dispersed by a planetary ball mill, and the composition of the porous back electrode layer slurry is shown in Table 3. The porous back electrode layer slurry is printed on the porous insulating spacer layer of the second preform by a screen printing machine. The second preform printed with the porous back electrode layer slurry is placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes to obtain a third preform with a porous back electrode layer. The third preform with a porous back electrode layer is annealed at 400°C for 30 minutes and cooled to room temperature.

[0130] (5) The iodine lead methylamine precursor slurry (the solvent is γ-butyrolactone, and the mass fraction of the solute is 30wt%) is applied to the porous back electrode layer by dispensing, and is allowed to penetrate into the pores of the porous electron transport layer, the porous insulating spacer layer, and the porous back electrode layer. The obtained product is annealed at 50°C for 10h to obtain a printable curved perovskite solar cell. Figure 1 shown.

[0131] (6) A polyurethane film (coating thickness of 0.5 mm) was covered on the porous back electrode layer of the printable curved perovskite solar cell, a flexible back panel was placed, and then laminated at 110° C. for 15 minutes to complete the encapsulation of the printable curved perovskite solar cell.

[0132] Example 2

[0133] The difference between Example 2 and Example 1 lies in step (2) to step (3). The details are as follows:

[0134] (1) Place the curved conductive substrate on III cleaning agent, ultrasonic cleaning for 15 minutes; then ultrasonic cleaning in ethanol for 10 minutes. The cleaned curved conductive substrate is dried at 55°C to obtain a clean curved conductive substrate. The cleaned curved conductive substrate is placed on a contoured fixture and fixed by vacuum adsorption. The conductive layer of the curved conductive substrate is laser etched by a nanosecond laser etcher to form an etched line P1. The width of the etched line P1 is 0.08mm. The curved conductive substrate with the etched line P1 is placed in deionized water and ultrasonically cleaned for 15 minutes; then ultrasonically cleaned in ethanol for 5 minutes. The cleaned curved conductive substrate with the etched line P1 is dried at 60°C to remove moisture and spot impurities on its surface. The dried curved conductive substrate with the etched line P1 is treated with ultraviolet and ozone for 15 minutes.

[0135] (2) Mix the raw materials of the porous electron transport layer slurry and vacuum degas for 45 minutes to obtain the porous electron transport layer slurry. The composition of the porous electron transport layer slurry is shown in Table 1. Use a screen printing machine to print the porous electron transport layer slurry on the conductive layer of the curved conductive substrate with the etched line P1. Evenly cover the polyurethane hot melt adhesive on the porous electron transport layer slurry, then place it in a vacuum drying oven and vacuum dry it at 100°C for 15 minutes. After the vacuum drying is completed, remove the polyurethane film to obtain the first preform with a porous electron transport layer. Anneal the first preform with a porous electron transport layer at 500°C for 30 minutes.

[0136] (3) The raw materials of the porous insulating spacer layer slurry are dispersed evenly by a planetary ball mill, and vacuum degassing is performed for 45 minutes to obtain a porous insulating spacer layer slurry. The composition of the porous insulating spacer layer slurry is shown in Table 2. The porous insulating spacer layer slurry is printed on the porous electron transport layer of the first preform by a screen printing machine. The polyurethane hot melt adhesive is evenly covered on the porous insulating spacer layer slurry, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes. After the vacuum drying is completed, the polyurethane film is removed to obtain a second preform having a porous insulating spacer layer.

[0137] (4) The porous back electrode layer slurry is dispersed by a planetary ball mill, and the composition of the porous back electrode layer slurry is shown in Table 3. The porous back electrode layer slurry is printed on the porous insulating spacer layer of the second preform by a screen printing machine. The second preform printed with the porous back electrode layer slurry is placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes to obtain a third preform with a porous back electrode layer. The third preform with a porous back electrode layer is annealed at 400°C for 30 minutes and cooled to room temperature.

[0138] (5) The iodine lead methylamine precursor slurry (the solvent is γ-butyrolactone, and the mass fraction of the solute is 30wt%) is applied to the porous back electrode layer by dispensing, and is allowed to penetrate into the pores of the porous electron transport layer, the porous insulating spacer layer, and the porous back electrode layer. The obtained product is annealed at 50°C for 10h to obtain a printable curved perovskite solar cell.

[0139] (6) A polyurethane film (coating thickness of 0.5 mm) is covered on the porous back electrode layer of the printable curved perovskite solar cell, a flexible backplane is placed, and then laminated at 110°C for 15 minutes to complete the encapsulation of the printable curved perovskite solar cell. In this embodiment, the viscosity of the porous electron transport layer slurry and the porous insulating spacer layer slurry is low at room temperature. After printing the above slurry, if it is left standing at room temperature, due to the curved structure of the substrate, the slurry flows severely, which is not conducive to the formation of the film. Therefore, this embodiment omits the step of standing at room temperature after printing the above slurry. In this way, a printable curved solar cell can be obtained. However, the surface of the resulting film will be relatively rough and the flatness will be poor.

[0140] Example 3

[0141] The difference between Example 3 and Example 1 lies in step (3) to step (4). The details are as follows:

[0142] (1) Place the curved conductive substrate on III cleaning agent, ultrasonic cleaning for 15 minutes; then ultrasonic cleaning in ethanol for 10 minutes. The cleaned curved conductive substrate is dried at 55°C to obtain a clean curved conductive substrate. The cleaned curved conductive substrate is placed on a contoured fixture and fixed by vacuum adsorption. The conductive layer of the curved conductive substrate is laser etched by a nanosecond laser etcher to form an etched line P1. The width of the etched line P1 is 0.08mm. The curved conductive substrate with the etched line P1 is placed in deionized water and ultrasonically cleaned for 15 minutes; then ultrasonically cleaned in ethanol for 5 minutes. The cleaned curved conductive substrate with the etched line P1 is dried at 60°C to remove moisture and spot impurities on its surface. The dried curved conductive substrate with the etched line P1 is treated with ultraviolet and ozone for 15 minutes.

[0143] (2) Mix the raw materials of the porous electron transport layer slurry, vacuum degassing for 45 minutes, and obtain the porous electron transport layer slurry. The composition of the porous electron transport layer slurry is shown in Table 1. The porous electron transport layer slurry is printed on the conductive layer of the curved conductive substrate with the etched line P1 using a screen printing machine. The curved conductive substrate after printing the porous electron transport layer slurry is allowed to stand at room temperature for 10 minutes, and then the polyurethane hot melt adhesive is evenly covered on the porous electron transport layer slurry, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes. After the vacuum drying is completed, the polyurethane film is removed to obtain the first preform having a porous electron transport layer. The first preform having a porous electron transport layer is annealed at 500°C for 30 minutes.

[0144] (3) The raw materials of the porous insulating spacer layer slurry are evenly dispersed by a planetary ball mill, and vacuum degassing is performed for 45 minutes to obtain a porous insulating spacer layer slurry. The composition of the porous insulating spacer layer slurry is shown in Table 2. The porous insulating spacer layer slurry is printed on the porous electron transport layer of the first preform by a screen printing machine. The first preform after printing the porous insulating spacer layer slurry is allowed to stand at room temperature for 10 minutes, and then the polyurethane hot melt adhesive is evenly covered on the porous insulating spacer layer slurry, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes. After the vacuum drying is completed, the polyurethane film is removed to obtain a second preform with a porous insulating spacer layer. A femtosecond laser etcher is used to etch on the second preform to form an etching line P2, and the etching line P2 is located on the left side of the etching line P1 and is tangent to the etching line P1, and the width of the etching line P2 is 0.5 mm.

[0145] (4) The porous back electrode layer slurry is dispersed by a planetary ball mill, and the composition of the porous back electrode layer slurry is shown in Table 3. The porous back electrode layer slurry is printed on the porous insulating spacer layer of the second preform having the etching line P2 by a screen printing machine. The second preform printed with the porous back electrode layer slurry is placed in a vacuum drying oven, vacuum dried at 100°C for 15 minutes, and cooled to room temperature to obtain a third preform having a porous back electrode layer. A femtosecond laser etcher is used to etch the third preform to form an etching line P3, which is located on the left side of the etching line P2 and tangent to the etching line P2. The width of the etching line P3 is 0.1 mm. The third preform having the etching line P3 is annealed at 400°C for 30 minutes and cooled to room temperature.

[0146] (5) The iodine lead methylamine precursor slurry (the solvent is γ-butyrolactone, and the mass fraction of the solute is 30 wt%) is applied to the porous back electrode layer by dispensing, and is allowed to penetrate into the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer, and then annealed at 50°C for 10 h to obtain a printable curved perovskite solar cell.

[0147] (6) A polyurethane film (coating thickness of 0.5 mm) was covered on the porous back electrode layer of the printable curved perovskite solar cell, a flexible back panel was placed, and then laminated at 110° C. for 15 minutes to complete the encapsulation of the printable curved perovskite solar cell.

[0148] Table 1

[0149] Example 1 Example 2 Example 3 Solvents α-Terpineol γ-Terpineol α-Terpineol Titanium dioxide solid content / wt% 4.5 4.5 4.5

[0150] Table 2

[0151] Example 1 Example 2 Example 3 Zirconium dioxide powder / weight 1 1 1 Ethyl cellulose (viscosity 10 cP) / weight 0.2 -- 0.2 Ethyl cellulose (viscosity 46 cP) / weight 0.1 0.3 0.1 α-Terpineol / weight 4 -- 4 γ-terpineol / weight -- 4 -- Glacial acetic acid / weight 0.5 1 0.5

[0152] Table 3

[0153] Example 1 Example 2 Example 3 Graphite powder 1 1 1 Carbon black powder 0.3 0.35 0.3 Zirconium dioxide powder 0.15 0.2 0.15 Ethyl cellulose (viscosity 10 cP) / weight 0.1 -- 0.1 Ethyl cellulose (viscosity 46 cP) / weight 0.05 0.15 0.05 α-Terpineol / weight 2 -- 2 γ-terpineol / weight 2 4 2 Glacial acetic acid / weight 0.15 0.3 0.15

[0154] Comparative Example 1

[0155] The difference between Comparative Example 1 and Example 1 is that the step of uniformly covering the porous electron transport layer slurry with the polyurethane hot melt adhesive is omitted. The details are as follows:

[0156] (1) Place the curved conductive substrate on III cleaning agent, ultrasonic cleaning for 15 minutes; then ultrasonic cleaning in ethanol for 10 minutes. The cleaned curved conductive substrate is dried at 55°C to obtain a clean curved conductive substrate. The cleaned curved conductive substrate is placed on a contoured fixture and fixed by vacuum adsorption. The conductive layer of the curved conductive substrate is laser etched by a nanosecond laser etcher to form an etched line P1. The width of the etched line P1 is 0.08mm. The curved conductive substrate with the etched line P1 is placed in deionized water and ultrasonically cleaned for 15 minutes; then ultrasonically cleaned in ethanol for 5 minutes. The cleaned curved conductive substrate with the etched line P1 is dried at 60°C to remove moisture and spot impurities on its surface. The dried curved conductive substrate with the etched line P1 is treated with ultraviolet and ozone for 15 minutes.

[0157] (2) The raw materials of the porous electron transport layer slurry are mixed and vacuum defoamed for 45 minutes to obtain the porous electron transport layer slurry. The composition of the porous electron transport layer slurry is shown in Table 1. The porous electron transport layer slurry is printed on the conductive layer of the curved conductive substrate with the etched line P1 using a screen printing machine. The curved conductive substrate after printing the porous electron transport layer slurry is left to stand at room temperature for 10 minutes, and then placed in a vacuum drying oven and vacuum dried at 100°C for 15 minutes.

[0158] The viscosity of the porous electron transport layer slurry decreases at 100°C. Since the conductive substrate is curved, without the auxiliary fixation of the polyurethane film, the slurry flows severely, and after drying, it is impossible to form a thin film on the curved conductive substrate, and the first preform with a porous electron transport layer cannot be obtained, and thus the curved perovskite solar cell cannot be prepared.

[0159] Experimental example

[0160] 1.1 Slurry viscosity test

[0161] The viscosity of the slurry at 18-40°C was tested using a Brookfield DV2TLV viscometer from the United States. Figure 3 and Figure 4 shown.

[0162] T11 represents the porous electron transport layer slurry of Example 1; T10 represents the porous electron transport layer slurry of Example 2; Z11 represents the porous insulating spacer layer slurry of Example 1; Z10 represents the porous insulating spacer layer slurry of Example 2.

[0163] Depend on Figure 3 It can be seen that the porous electron transport layer slurry is significantly affected by temperature. As the temperature rises, the viscosity of the porous electron transport layer slurry decreases. When the temperature rises to 40°C, the viscosity of T10 is only 110cP, and the viscosity of T11 is about 510cP. The fluidity of T10 and T11 can meet the conditions for curved surface printing, but T11 is more controllable, which is conducive to the uniformity of film formation. At room temperature (25°C), the viscosity of T10 is about 450cP, and the viscosity of T11 is about 1800cP. The viscosity of T11 increases significantly and the fluidity decreases significantly, which is conducive to the controllability of the film at room temperature, thereby making the film formation more uniform.

[0164] Depend on Figure 4 It can be seen that the porous insulating spacer slurry is significantly affected by temperature. As the temperature rises, the viscosity of the porous insulating spacer slurry decreases. When the temperature rises to 38°C, the viscosity of Z11 is about 50,000 cP, and its fluidity is much lower than that of Z10. Z11 can not only meet the requirements of curved surface printing, but also improve the controllability of the film. At room temperature (25°C), the viscosity of Z11 is about 100,000 cP, and the viscosity of Z10 is about 50,000 cP. The viscosity of Z11 is about twice that of Z10. The film formed by Z11 has strong controllability, which is conducive to increasing the uniformity of film formation.

[0165] 1.2 Porous electron transport layer film thickness test

[0166] The first preform was cooled to room temperature, and a 10 cm × 10 cm area was selected on the surface of the first preform. A cross-shaped etching network was etched in the selected area using a femtosecond laser etcher, and then the thickness of the porous electron transport layer was tested using a German Bruker probe step profiler (model: Dektak XT). Based on the film thickness data of the porous electron transport layer in the test surface, a three-dimensional contour morphology of the porous electron transport layer was drawn.

[0167] Figure 5 This is a three-dimensional profile image of the porous electron transport layer of Example 1. Figure 6 This is a three-dimensional contour morphology image of the porous electron transport layer of Example 2.

[0168] Depend on Figure 5 and Figure 6 It can be seen that the thickness of the porous electron transport layer of Example 1 is about 550nm, the surface and the surroundings are relatively flat, and the film uniformity is good. The thickness of the porous electron transport layer of Example 2 is about 600nm, the surface thickness fluctuates greatly, the slurry loss at the edge is serious, and the film thickness is only 300nm, which is more than 300nm different from the center.

[0169] 1.3 Porous insulation spacer film thickness test

[0170] The second preform was cooled to room temperature, and a 10 cm × 10 cm area was selected on the surface of the second preform. A cross-shaped etching network was etched in the selected area using a femtosecond laser etcher, and then the thickness of the porous electron transport layer was tested using a German Bruker probe step profiler. Based on the thickness data of the porous electron transport layer in the test surface, a three-dimensional contour morphology of the porous electron transport layer was drawn.

[0171] Figure 7 This is a three-dimensional profile image of the porous electron transport layer of Example 1. Figure 8 This is a three-dimensional contour morphology image of the porous electron transport layer of Example 2.

[0172] Depend on Figure 7 and Figure 8 It can be seen that the thickness of the porous insulating spacer layer of Example 1 is about 2.2 μm, the surface and the surroundings are relatively flat, and the porous film has good uniformity. The thickness of the porous insulating spacer layer of Example 2 fluctuates greatly, and the film thickness distribution in the test area is between 2.0 and 4.0 μm. This is mainly due to the good fluidity of the slurry, which causes the slurry to flow and aggregate. The film thickness at the edge is 4.0 μm, and the film thickness at the center is 2.0 μm, with a thickness difference of more than 2.0 μm.

[0173] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing a printable curved perovskite solar cell, characterized in that: A printable curved perovskite solar cell comprises a curved conductive substrate, a porous electron transport layer, a porous insulating spacer layer, a porous back electrode layer and a perovskite filler; the curved conductive substrate comprises a curved transparent substrate and a conductive layer deposited on the curved transparent substrate; the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer are sequentially deposited on the conductive layer from bottom to top; the perovskite filler is filled in the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer; wherein the thickness of the porous electron transport layer is 300 to 1000 nm, the thickness of the porous insulating spacer layer is 1 to 6 μm, and the thickness of the porous back electrode layer is 10 to 40 μm; the preparation method comprises the following steps: (1) Laser etching a clean curved conductive substrate to form an etching line P1; (2) Covering the porous electron transport layer slurry on the conductive layer of the curved conductive substrate having the etched line P1, and then covering the porous electron transport layer slurry with hot melt adhesive to form a first hot melt adhesive film; removing the first hot melt adhesive film to obtain a first preform having a porous electron transport layer; (3) covering the porous insulating spacer layer slurry on the porous electron transport layer of the first preform, and then covering the second hot melt adhesive on the porous insulating spacer layer slurry to form a second hot melt adhesive film; removing the second hot melt adhesive film to obtain a second preform having a porous insulating spacer layer; (4) covering the porous back electrode layer slurry on the porous insulating spacer layer of the second preform to form a porous back electrode layer, thereby obtaining a third preform having a porous back electrode layer; (5) Applying the perovskite precursor slurry to the porous back electrode layer of the third preform so that the perovskite precursor slurry fills the pores of the porous electron transport layer, the porous insulating spacer layer and the porous back electrode layer to obtain a printable curved perovskite solar cell.

2. The preparation method according to claim 1, characterized in that: The first hot melt adhesive and the second hot melt adhesive are independently selected from one of polyurethane, polyolefin elastomer, polyethersulfone resin, copolyamide, ethylene-acrylic acid copolymer or ethylene-vinyl acetate copolymer.

3. The preparation method according to claim 1, characterized in that: The porous electron transport layer slurry comprises an electron transport material and pine alcohol, and the solid content of the electron transport material in the porous electron transport layer slurry is 2 to 10 wt %; The pineol contains α-pineol, and the content of the α-pineol in the pineol is more than 30wt%; The electron transport material is selected from one or more of titanium dioxide, tin dioxide, zinc oxide or barium stannate.

4. The preparation method according to claim 1, characterized in that: The porous insulating spacer layer slurry comprises insulating material, ethyl cellulose and pinene alcohol; wherein the mass ratio of the insulating material to the ethyl cellulose is 1:0.15-0.4, and the mass ratio of the insulating material to the pinene alcohol is 1:2-6; the insulating material is selected from one or more of zirconium dioxide, silicon dioxide, aluminum oxide or barium titanate; the pinene alcohol contains α-pinene alcohol, and the content of the α-pinene alcohol in the pinene alcohol is above 30wt%; The porous back electrode layer slurry comprises graphite, carbon black, zirconium dioxide, ethyl cellulose and terpineol; The mass ratio of the graphite to carbon black is 1:0.15-0.5, the mass ratio of the graphite to zirconium dioxide is 1:0.1-0.5, the mass ratio of the graphite to ethyl cellulose is 1:0.1-0.5, and the mass ratio of the graphite to terpineol is 1:2-6.

5. The preparation method according to claim 4, characterized in that: The porous insulating spacer layer slurry also includes glacial acetic acid, and the mass ratio of the insulating material to the glacial acetic acid is 1:0.05-1; The porous back electrode layer slurry also includes glacial acetic acid, and the mass ratio of the graphite to the glacial acetic acid is 1:0.01-0.

6.

6. The preparation method according to claim 1, characterized in that: The following steps are also included: The first preform having the porous electron transport layer is annealed at 300-600° C. for 10-60 min and then used in step (3).

7. The preparation method according to claim 1, characterized in that: The following steps are also included: Laser etching on the second preform having the porous insulating spacer layer to form an etched line P2; The etching line P2 is located on the left side of the etching line P1 and is tangent to the etching line P1; the width of the etching line P2 is 0.3-1 mm.

8. The preparation method according to claim 7, characterized in that: The following steps are also included: Laser etching is performed on the third preform having the porous back electrode layer to form an etched line P3, and then annealing is performed at 300-600° C. for 10-60 min; The etching line P3 is located on the left side of the etching line P2 and is tangent to the etching line P2. The width of the etching line P3 is 0.05-0.3 mm.

Citation Information

Patent Citations

  • Novel all-solid-state printable perovskite solar cell based on carbon electrode

    CN107146847A

  • Perovskite solar battery module

    CN108550705A

  • Flexible mica transparent solar cell prepared at high temperature in large scale

    CN109860400A

  • All-printed mesoscopic perovskite solar cell adopting carbonyl small molecules as additive and preparation method thereof

    CN111223994A